Employer Branding dalam Menarik Generasi Z di Dunia Kerja - Sunarto Sunarto; Goutty Ranti (Green Publisher Indonesia, 2026)
The rapid development of digital technology has transformed the dynamics of the workforce, especially with the entry of Generation Z into the job market. Generation Z has distinct characteristics and expectations compared to previous generations, such as prioritizing work-life balance, transparency, and alignment with personal values. In this context, employer branding plays a crucial role in attracting the attention of this generation. This study aims to examine the role of employer branding in attracting Generation Z to the workplace and to analyze effective strategies for building a positive image as an employer. The research uses a quantitative approach with the type of explanatory research. Data was collected through questionnaires distributed to Generation Z respondents, especially final year students and fresh graduates, then analyzed using statistical techniques. The findings reveal that strong employer branding increases Generation Z's interest in applying for jobs, with social media serving as the primary channel for conveying company information. Additionally, the alignment of individual values with the organization is essential in enhancing attraction to the company. This research provides insights for companies to design relevant and authentic employer branding strategies to attract top talent from Generation Z.